Heterologous expression of the insect SVWC peptide WHIS1 inhibits Candida albicans invasion into A549 and HeLa epithelial cells - Chen, Ming; Huang, Wei-Kang; Yao, Yang; Wu, Shi-Mei; Yang, Yong-Xin; Liu, Wen-Xia; Luo, Gang; Wei, Shao-Feng; Zhang, Hua; Liu, Hong-Mei; Wang, Bing (Frontiers in Microbiology, 2024)
Candida albicans (C. albicans), a microbe commonly isolated from Candida vaginitis patients with vaginal tract infections, transforms from yeast to hyphae and produces many toxins, adhesins, and invasins, as well as C. albicans biofilms resistant to antifungal antibiotic treatment. Effective agents against this pathogen are urgently needed. Antimicrobial peptides (AMPs) have been used to cure inflammation and infectious diseases. In this study, we isolated whole housefly larvae insect SVWC peptide 1 (WHIS1), a novel insect single von Willebrand factor C-domain protein (SVWC) peptide from whole housefly larvae. The expression pattern of WHIS1 showed a response to the stimulation of C. albicans. In contrast to other SVWC members, which function as antiviral peptides, interferon (IFN) analogs or pathogen recognition receptors (PRRs), which are the prokaryotically expressed MdWHIS1 protein, inhibit the growth of C. albicans. Eukaryotic heterologous expression of WHIS1 inhibited C. albicans invasion into A549 and HeLa cells. The heterologous expression of WHIS1 clearly inhibited hyphal formation both extracellularly and intracellularly. Furthermore, the mechanism of WHIS1 has demonstrated that it downregulates all key hyphal formation factors (ALS1, ALS3, ALS5, ECE1, HWP1, HGC1, EFG1, and ZAP1) both extracellularly and intracellularly. These data showed that heterologously expressed WHIS1 inhibits C. albicans invasion into epithelial cells by affecting hyphal formation and adhesion factor-related gene expression. These findings provide new potential drug candidates for treating C. albicans infection.